Pelatihan Microsoft Excel Untuk Kalangan Murid Kelas 9 SMPS Al-Hasyimiyah Bojong Gede - Randy Cansera; Andi Salwa Assyifa; Muhammad Akbar Alhafid; Muhamad Irham Azikri; Ricky Sutjipto Nurdjaya; Sendy Bahri; Yosafat Yusak Junior; Zaynudin (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Community service activities become very important when the service team can share their knowledge with the community. In this case, the service team carried out activities at SMPS Al-Hasyimiyah Bojong Gede. The implementation method was in the form of presentations, discussions, and training for students, especially for making Microsoft Excel spreadsheets and formulas. The results obtained from this task are that it allows students to create spreadsheets and formulas for data processing.